Effect of pearling on composition, microstructure, water migration and cooking quality of highland barley (Hordeum vulgare var. Coeleste Linnaeus). (30th November 2022) - Li, Meng-jia; Shan, Lei; Tong, Li-Tao; Fan, Bei; Liu, Li-ya; Sun, Ruo-qi; Huang, Ya-Tao; Wang, Feng-zhong; Wang, Li-li
Highlights: Pearling reduced the proportion of nutrients except starch and β-glucan. The bran could be basically removed by pearling 30% of the highland barley weight. Removing the pericarp could greatly shorten the cooking time of highland barley. The Peleg model can well-fit simulate the water absorption during cooking of highland barley. The moderately bound water increased the most of highland barley during cooking. Abstract: Highland barley (HB) has become popular due to its nutritional benefits, and pearling as a necessary process that could broaden its applications. The influence of pearling on the composition, microstructure, water migration and cooking characteristics of HB was investigated. With different degrees of pearling (DOPs), the levels of nutritious components except for starch and β-glucan, decreased, and the β-glucan content gradually increased and reached a plateau when the DOP was over 15%. Pearling can significantly shorten the cooking time by removing different tissues, and removal of the pericarp layer had significant influence by reducing the cooking time by 17 min (i.e., HB with DOP 5%). From the result of Peleg model fitting and low-field nuclear magnetic resonance spectroscopy, the saturated water absorption of HB did not differ for a DOP 5% and above, and cooking mainly increased the amount of moderately bound water and added small amount of bound water.